(untitled) (Bangladesh Journal of Pharmacology, 2014)
The present study evaluated the hypoglycemic effect of brown algae Sargassum longiotom in alloxan-induced diabetic rats. After the treatment with S. longiotom extract, there is a significant reduction (p<0.001) in blood glucose when compared with the diabetic control group. Moreover the ethanolic extract of S. longiotom significantly reduces (p<0.001) the levels of triglycerides, low-density lipoprotein cholesterol and very low-density lipoprotein cholesterol dose dependent manner. Alternatively, it increases the high-density lipoprotein cholesterol level in the treated groups. The values of SGOT, SGPT and ALP have been significantly reduced (p<0.001) in the treated rats when compared to diabetic control. Thus, the present study indicates that the ethanolic extract of seaweed S. longiotom posses very effective hypoglycemic and hypolipidemic effect on the alloxan-induced diabetic rats compared to the reference drug glibenclamide.